Anti-n-methyl-d-aspartate receptor encephalitis presenting as postpartum psychosis: A case report (Indian Journal of Case Reports, 2020)
Anti-N-methyl-d-aspartate (NMDA) receptor encephalitis is a form of encephalitis occurring primarily in women and associated with antibodies against NR1 or NR2 subunits of the NMDA receptor. As psychiatric symptoms may predominate at the onset or over the course of the disease, the diagnosis is frequently delayed. Yet, the patients’ prognosis depends on the speed with which the disease is detected, identified, and managed. Because the presence of pronounced psychiatric symptoms drives the patients to psychiatric institutions, physicians need to be aware of autoimmune encephalitis and propose the detection of autoantibodies as early as possible to provide optimal medical care to such patients. Here, we report the case of a 24-year-old female who presented to the hospital with symptoms suggestive of postpartum psychosis but further investigations revealed her to be positive for anti-NMDA receptor autoantibodies.